“Métodos de control de malezas en el cultivo de frijol caupí, variedad blanco cumbaza-INIA (vigna unguiculata (L) walp) en el bajo mayo”- Tarapoto región San Martín” - Delgado Tello, Helder Roberto (2003)
The present research work executed in the Oasis Sector, Km 2, • i 1 marginal road •, on the ground of the Minis ~ erio's fishery, entregapo in transfer of use to the National University of San Martín, whose geographical position is following ·the: length West 76 ° 23' South latitude 6 ° 29' '. Altitude of 350 m.a.s.l. Tropical dry forest the objective of this thesis work, had intended to assess the best weed control system. and determine the relationship cost J benefit of the best treatment. P.ARA the establishment of est ~ work was used as bean cowpea seed variety white Cumbaza - INIA, settling the growing el·dia-· June 2000, performing the harvest in two phases the 07-12 August the mismb year •... ·, OTde. l respectively. The experimental design to be. used was complete blocks rando.mizados 04 repetitions and 06 treatments. ·Low study treatments were: l. chemical LINURON (AFALON), 2.0 kg. p.c. / has 2. D ...